Highly Enantioselective Organocatalytic Michael Addition of Ketones to Nitroolefins in the Presence of Water - Chen, Qiankun; Qiao, Yupu; Ni, Bukuo (Synlett, 2013)
Chiral pyrrolidine-based organocatalysts, in combination with ionic-liquid-supported Brønsted acids, catalyze the enantioselective Michael addition of ketones and aldehyde to nitroolefins in high yields with high enantioselectivities (ee ≤ 96%) and diastereoselectivities (syn/anti ratio ≤ 98:2). This novel process provides synthetically useful γ-nitrocarbonyl compounds, which can be easily transformed into other invaluable precursors of biologically active compounds. In addition, the synthetic procedure presented is simple and practical.
Keywords: organocatalysts; asymmetric synthesis; Michael addition; ketones; nitroolefins